Model Pembelajaran Tipe Think Talk Write (TTW) Untuk Meningkatkan Hasil Belajar Siswa - Nadilah Nadilah; Kasma F Amin; Nurmiah Muin (Phonologie : Journal of Language and Literature, 2022)
Abstract. This research aims to describe students' ability to improve learning outcomes by using methods (Think, Talk, Write) in students of class X IPS 1 SMA Negeri 16 Makassar. This class action research has four stages of procedure that is. The subject in the study was class X IPS 1 sma Negeri 16 Makassar who numbered 36 students. Then the data is analyzed using quantitative and qualitative description analysis. The results showed that the activities shown by students from activities carried out in cycles 1 to cycle 2 showed different attitudes. After the action is carried out in cycle 2 students become more active in learning, students are not only silent as in cycle 1 but students also follow the instructions of researchers, besides that students also show interest and enthusiasm in the learning process. Student spirit is more visible and students more often ask related questions that are not yet understood. Student test score results at the time of student presiklus activities that reached KKM as many as 2 students or 5%, in cycle 1 student activities that reached KKM as many as 11 students or 44%, in cycle 2 students who reached KKM as many as 22 students.Keyword: Learning model, Learning outcomes, Think Talk Write (TTW)